Performance assessment of high-rate GPS/BDS precise point positioning for vibration monitoring based on shaking table tests. Issue 6 (15th March 2022) - Yu, Wenkun; Peng, Hui; Pan, Lin; Dai, Wujiao; Qu, Xuanyu; Ren, Zhao
Abstract: For modern engineering infrastructures, the vibration information is critical in identifying the dynamic characteristics and assessing the structural health. Over the past few decades, Global Navigation Satellite System (GNSS) has played an increasingly important role in the monitoring of surface dynamic movement. The GNSS-based precise point positioning (PPP) has received much attention due to its technical feasibility and economic efficiency. More efforts are expected to be made in the research of high-rate PPP and the integration of multiple GNSSs for structural health monitoring. This study evaluates the performance of GPS/BDS kinematic PPP with 20-Hz observations in capturing vibrations generated from a linear shaker. A comparative analysis of the solutions obtained from GPS/BDS high-rate PPP, real-time kinematic (RTK) positioning, total station and accelerometer is performed in both frequency and displacement domains. The experimental results show that the displacement time series captured by GPS/BDS PPP and RTK can achieve an accuracy of 5.7–8.4 and 4.5–6.6 mm with respect to those from total station, respectively. The PPP-derived vibration frequency is consistent with that from RTK, total station and accelerometer, with a deviation less than 0.008 Hz among each other. For comparison, the GPS-only and BDS-only PPP results are also provided, and it is indicated that the dual-system integration can enhance the reliability and accuracy of monitoring results. For completeness, another experiment is conducted to investigate the performance difference between ambiguity-float and ambiguity-fixed PPP for vibration monitoring.